Annual Abstract of Statistics 1981 (Lagos : Federal Office of Statistics, 1981)
1969 edition of the annual abstract of statistics prepared by the Federal Office of Statistics, Lagos.
rpm 19/02/2019
Loans
Keywords: Industrial statistics; Population--Statistics; Statistics; Nigeria